2010
DOI: 10.1177/1352458510378126
|View full text |Cite
|
Sign up to set email alerts
|

The effect of core stability training on balance and mobility in ambulant individuals with multiple sclerosis: A multi-centre series of single case studies

Abstract: This study provides preliminary evidence of the effectiveness of an 8-week core stability training programme in improving balance and mobility in ambulant people with MS. Variations in response to intervention are evident. Assessor-blinded randomized controlled studies are required to confirm these findings and determine patient characteristics which identify those who benefit most from this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 33 publications
4
72
1
3
Order By: Relevance
“…Other studies 12,17,22,23 who have included subjects with similar levels of disability have also reported large standard deviations. Thus even with a narrow EDSS range (5-6.5) heterogeneity was event within the sample.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other studies 12,17,22,23 who have included subjects with similar levels of disability have also reported large standard deviations. Thus even with a narrow EDSS range (5-6.5) heterogeneity was event within the sample.…”
Section: Discussionmentioning
confidence: 98%
“…Cattaneo et al 3 did not find any significant difference in the results of the ABC questionnaire over time, nor did Freeman et al 22 whose participants (with a similar disability level to our subjects) followed eight weeks of one to one out-patient physiotherapy core balance sessions, with additional home exercises. The ABC includes questions in relation to everyday experiences (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of on MS patients have been studied [12] and incremental improvements in body balance, joint mobility and upper body muscle strength have been observed. Marandi et al [13] compared the Pilates method with microgravity exercises among MS patients and the outcomes revealed positive benefits on dynamic body balance, in keeping with Freeman et al [14], who demonstrated that Pilates also positively influences ambulation. Moreover, 10 weeks of proprioceptive training prove to be efficacy in the improvement of the stability and in the reduction of the energy required to maintain it [15].…”
Section: Journal Of Neurology and Neurophysiologymentioning
confidence: 71%
“…Lim et al [31] studied the effect of a Pilates protocol on nineteen individuals affected by unilateral chronic hemi-paretic strokes, and they highlighted significant improvements in both static and dynamic body balance. However, among the MS patients involved in this study, this technique was useful in improving performance in the Sit and Reach and the Sit to Stand test after 16 weeks of training, with no effects on body balance, confirming the greater utility of other training methods to this end, such as core stability [14]. Our outcomes seem to be consistent with a previous study [32] which revealed the great importance of Pilates in the improvement of performance in the sit to stand test after 8 weeks of training.…”
Section: Discussionmentioning
confidence: 93%